Studying More to Vote Less: Education and Voter Turnout in Italy - Elona Harka; Lorenzo Rocco (Institute of Labor Economics (IZA), 2019)
We use Italian municipality data on education and voter participation in national elections to estimate the effect of schooling on voter turnout. By adopting a fixed effect instrumental variable identification strategy, we find that education reduces voter turnout, more so in municipalities with higher income, lower social capital, which experienced political misconduct in the past and have low institutional quality. Analysis with individual data confirms these results. We discuss several mechanisms to rationalize our findings ranging from the opportunity cost of time to disaffection and civic protest.
Keywords: I20; I26; D72; 330; voter turnout; education; Italy; protest